Evolutionary psychology : an introduction - Workman, Lance (Cambridge University Press, 2004)
This textbook offers a comprehensive and accessible introduction to the complex but fascinating science of evolutionary psychology. By focusing on the way mind and behavior have developed and adapted to evolutionary pressures the authors show the relevance of an evolutionary approach to all areas of psychology and have created a stand-alone text that will also complement traditional courses. Not only are standard topics such as natural selection and sexual selection covered but also areas where there has been much exciting new research such as the evolution of the emotions, evolution and child development, the evolution of language and Darwinian medicine. The authors' objective perspective will be much appreciated in this often controversial area as will their engaging style and the user-friendly format. Each chapter features a preview and list of key terms, boxes highlighting case studies and the latest research, a summary and a guide to further reading.